The impact of use the picturistic cards in developing conversation skills of kindergarten child Field study in Homs city - Barakat , Ghassan; Ismail , Mohamed; Eddin, Samar Musa Saad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to planning picture cards to develop the conversation skills of kindergarten children, And to know the impact of use cards for the kindergarten child in the development of skills especially conversation and development through the way of fun and play. The researcher noticed a clear improvement in conversation skill of among the sample members following the use of photo cards as important activities in relation to the educational return achieved by the children through the practice of these activities based on the picturistic stories with vocabulary included on it. In addition, the achievement of other educational goals of values, trends and concepts have a positive impact on the personality of the child. The study was conducted in the city of Homs on a sample of children aged 5-6 years to develop their vocabulary and increase their linguistic quotient, which led to improved conversation skills. The tools were designed to fit subjects consistent with the Ministry of education's planned experiences , and analyzed results using percentages and T test. The study concluded that: The need to produce such picture cards and train teachers to use them and avoid traditional education.